Dual-layer remote phosphor structure: a novel technique to enhance the color quality scale and luminous flux of WLEDs - Phung Ton That; Thuc Minh Bui; Nguyen Thi Phuong Loan; Phan Xuan Le; Nguyen Doan Quoc Anh; Le Van Tho (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The effects of red light-emitting phosphor CaMgSi2O6:Eu2+,Mn2+ on the optical properties of single-layer remote phosphor structure (SRPS) and dual-layer remote phosphor structure (DRPS) are the focus of this study. The differences in color quality and luminous flux (LF) of white light-emitting diodes (WLEDs) between these two structures are also revealed and demonstrated based on the Mie theory. SRPS consists of one mixed phosphor layer betweenCaMgSi2O6:Eu2+,Mn2+ andYAG:Ce3+particles, while DRPS includes two separated layers: red phosphor layer and yellow phosphor layer. In this work, 5% SiO2 is added into the phosphor layers to increase scattering abilities. Discrepancies in structures greatly affect the optical characteristics of WLEDs. The results showed that the color rendering index (CRI) increased with the concentration in both structures with nearly equal values. Meanwhile, color quality scale (CQS) of DPRS is 74 at ACCTs ranging from 5600K to 8500K, higher than CQS of SRPS which is only 71 at 8500K. In addition, the luminous flux of DRPS is significantly higher than SRPS at 2% -14% of CaMgSi2O6:Eu2+,Mn2+. In summary, DRPS is better for color quality and lumen outputin comparison to SRPS and adding the right amount of red phosphor can enhance CQS and LF.